(untitled) (Altre Modernità, 2022)
The intervention aims at a reconstruction, albeit partial, of the thought of the last Baudrillard and of the relationship between his theory of the image and the traumatic dimension to which is linked in various ways. The first part analyzes the imaginary trauma that forced him to a “lacerating revision” of his own thought that pushed him to change the sign of some of his interpretative constants. The second part defines the dual and viral dialectic of image and return-image as the horizon of the original trauma that persists: the primitive scene of absence. The conclusion is an ideal non-answer to the Baudrillardian question par excellence: to what extent can thought respond to an event with an analysis that is as unacceptable as the event itself?